Dampak Psikologis Kekerasan Orang Tua Terhadap Anak - Matondang, Fatiha Sabila Putri; Alfira, Niza; Mardhyah, Dwi Putri; Harahap, Muhammad Riski; Khatami, Mulkan (Polyscopia, 2024)
Parental violence against children has been a prevalent issue with far-reaching impacts on child development. This study explores the effects of such violence on children’s psychological well-being through a systematic literature review, focusing on physical, psychological, and social dimensions. The research problem addresses the need for a deeper understanding of how parental violence shapes children’s self-esteem, social interactions, and overall mental health. Thematic analysis was employed to categorize findings, revealing significant adverse effects across multiple domains, including increased anxiety, social withdrawal, and reduced self-worth. These findings underscore the critical need for preventive interventions to safeguard children’s psychological welfare. The study concludes with a call for further research and community-based preventive measures to address and mitigate these impacts.